2012
DOI: 10.1111/irv.12056
|View full text |Cite
|
Sign up to set email alerts
|

A study of Chitosan and c‐di‐GMP as mucosal adjuvants for intranasal influenza H5N1 vaccine

Abstract: Please cite this paper as: Svindland et al. (2012) A study of Chitosan and c‐di‐GMP as mucosal adjuvants for intranasal influenza H5N1 vaccine. Influenza and Other Respiratory Viruses 10.1111/irv.12056000(000), 000–000. Background  Highly pathogenic avian influenza A/H5N1 virus remains a potential pandemic threat, and it is essential to continue vaccine development against this subtype. A local mucosal immune response in the upper respiratory tract may stop influenza transmission. It is therefore important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 60 publications
(129 reference statements)
5
26
1
Order By: Relevance
“…This was verified further by the detection of (IL‐2 and TNF‐ α ) double‐producing multifunctional Th1 CD4 + cells that were significantly higher in the intranasal group, while (IFN‐ γ , IL‐2 and TNF‐ α ) multifunctional Th1 CD4 + cells were present in comparable amounts in both the intranasal and intramuscular group. This is consistent with our previous reports, where multifunctional Th1 CD4 + cells were detected in response to a c‐di‐GMP‐adjuvanted H5N1 influenza vaccine administered intranasally, intramuscularly and sublingually . Moreover, we have also shown that a virosomal H5N1 influenza vaccine induces a balanced Th1/Th2 profile both in mice and in humans, when adjuvanted with Matrix‐M .…”
Section: Discussionsupporting
confidence: 93%
“…This was verified further by the detection of (IL‐2 and TNF‐ α ) double‐producing multifunctional Th1 CD4 + cells that were significantly higher in the intranasal group, while (IFN‐ γ , IL‐2 and TNF‐ α ) multifunctional Th1 CD4 + cells were present in comparable amounts in both the intranasal and intramuscular group. This is consistent with our previous reports, where multifunctional Th1 CD4 + cells were detected in response to a c‐di‐GMP‐adjuvanted H5N1 influenza vaccine administered intranasally, intramuscularly and sublingually . Moreover, we have also shown that a virosomal H5N1 influenza vaccine induces a balanced Th1/Th2 profile both in mice and in humans, when adjuvanted with Matrix‐M .…”
Section: Discussionsupporting
confidence: 93%
“…These results parallel recent studies evaluating the beneficial effects of direct administration of c-di-GMP as an adjuvant during vaccination with OVA (49, 50), and 4-Hydroxy-3-nitrophenylacetyl-Chicken Gamma Globulin, NP-CGG, in which c-di-GMP was shown to have the capacity to enhance germinal center (GC) development (67). Additionally, the presence of c-di-GMP in an adjuvant formulation containing chitosan (CSN) improved adaptive immune responses to H5N1 antigens (16), and (along with a conventional aluminum salt-based adjuvant) improved adaptive immune responses specific to the hepatitis B surface antigen (HBsAg) (67). Recently, it was demonstrated that nasal administration of c-di-GMP significantly increases the MYPS-mediated uptake of OVA antigen via endocytosis and pinocytosis in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The direct administration of c-di-GMP has been shown to induce innate immune responses that can enhance protection of mice against challenges with Klebsiella pneumoniae (10), Staphylococcus aureus (11), methicillin-resistant S. aureus (MRSA) (12), Bordetella pertussis (13), Streptococcus pneumoniae (14), and avian influenza A/H5N1 (15, 16). Specifically, following intranasal challenge with B. pertussis in BALB/c mice, c-di-GMP induced production of cytokines such as IFN-γ, TNF-α, IL-6, and the chemokine MCP-1 in lung tissue (13).…”
Section: Introductionmentioning
confidence: 99%
“…It served as an immunopotentiating agent to augment vaccine immunogenicity and effectiveness (23). Besides, annotated data have demonstrated that the CS nanoparticles induced both mucosal and systemic immune responses to the entrapped antigen after intranasal administration (24,25). In this study, a split influenza vaccine containing hemagglutinin of H1N1 virus formulated with CS nanoparticles was administered intranasally.…”
Section: Introductionmentioning
confidence: 96%